Rancang Bangun Alat Bantu Meja Lift Otomatis Pengangkut Silinder Menggunakan Sistem Linear Aktuator Elektrik - Al'ma Arif Arrahman; Mohamad Hakam; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
CV. Setia Abadi Printing is a company that engaged in the packaging industry. The machine used by this company is a rotogravure printing machine, most of which are desingned and made personally by the owner of the company. The cylinder component is an important part of the rotogravure printing machine because in the production process the cylinder component is in direct contact with the production material, namely plastic. In transporting cylinder components, employees still use manual labor from the workshop area to the production area with a distance of 350 meters and the weight of the cylinder components reaches 50 kg, so it is very ineffective and waste a lot of manpower. The method used by the author is the Ulrich method through the selection of several design concepts, the design of which is assisted by CAD software for drawing, fabrication, assembly of machine components and tool testing to determine the production results of the tool. Based on the results of planning and design that has been done, the dimensions of the tool with the main dimension 1395 mm x 580 mm x 1092 mm. For drive is designed using a linear system of electric actuators. In the prototype test the automatic lift table tool cylinder transporter using a linear system of electric actuators was able to carry a load of 50 kg and lifted as high as 1 meter.